Work-life balance in Malaysia : An introduction - Hassan, Zaiton; Dollard, Maureen F. (2007)
The paper discusses the concept of Work-Life Balance (WLB), why it is receiving more attention at work and in the society, the benefits it brings to organisations and employees as well as issues surrounding WLB. To illustrate an example, WLB policies in Malaysia, namely maternity leave and on-site child care centre in comparison with other countries are highlighted. Although WLB policies are implemented in Malaysia, they are inconsistent and not supportive of one another. For instance, generosity in maternity leave is not supported with on-site child care facilities in the workplaces.